Revising the taxonomy of Proceratophrys Miranda‐Ribeiro, 1920 (Anura: Odontophrynidae) from the Brazilian semiarid Caatinga: Morphology, calls and molecules support a single widespread species. (20th January 2020) - Mângia, Sarah; Oliveira, Eliana Faria; Santana, Diego José; Koroiva, Ricardo; Paiva, Fernando; Garda, Adrian Antonio
Abstract: Recently, Proceratophrys cristiceps was redescribed along with the description of two species from the Caatinga biome: P. aridus and P. caramaschii . However, only a small fraction of the populations related to such species in Northeastern Brazil was examined, and most populations of central Caatinga were not contemplated in this analysis. Comparisons were also based exclusively on external morphology, precluding a more accurate delimitation of such taxa in the light of multiple characters. Such geographic paucity and reliance in only one data source caused the species status of most central Caatinga populations to be uncertain. Thus, the revision of Proceratophrys populations from the Caatinga biome is of utmost importance to establish a solid taxonomic background and to test the validity of the described species. Based on morphologic, morphometric, acoustic, and multilocus genetic data, we define the range of inter‐ and intrapopulation variation in the parameters we analyzed, establishing which ones are useful as diagnostic characters for Proceratophrys in the Caatinga. We found no evidence supporting P. aridus and P. caramaschii as distinct species and thus place them as junior synonyms of P. cristiceps . Our results reinforce the importance of using multiple lines of evidence to avoid taxonomic instability. Abstract : Proceratophrys cristiceps was redescribed along with the description of two species from the Caatinga biome: P. aridus and P. caramaschii . Based on morphologic, morphometric, acoustic, and multilocus genetic data of these three species, we found no evidence supporting P. aridus and P. caramaschii as distinct species and thus place them as junior synonyms of P. cristiceps . Our results reinforce the importance of using multiple lines of evidence to avoid taxonomic instability.